1990
DOI: 10.1177/0148607190014005467
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Infusion of Long‐ and Medium‐Chain Triglycerides and Reticuloendothelial System Function in Man

Abstract: Previous study demonstrated that patients who received total parenteral nutrition (TPN) with standard intermittent infusion of long chain triglyceride (LCT) at 0.13 g kg-1hr-1 over 10 hr for each of three days showed a significant decline in 99Tc-sulfur colloid (TSC) clearance rate by the reticuloendothelial system (RES). The present studies evaluated eight patients who received the same total lipid dose of LCT infused continuously as in a three-in-one admixture, and another nine patients receiving the same am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
4

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 16 publications
0
54
0
4
Order By: Relevance
“…Opsonins appear not to be involved in HSA-MM clearance, but it is still unclear which receptor may indeed be involved [ 171. Seidner et al [29] and Jensen et al [12] used TSCs in their studies, but these appear unsuitable for macrophage function assessment. In studies by Hirschberg et al [14], TSCs were cleared from the bloodstream with nonsaturable kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Opsonins appear not to be involved in HSA-MM clearance, but it is still unclear which receptor may indeed be involved [ 171. Seidner et al [29] and Jensen et al [12] used TSCs in their studies, but these appear unsuitable for macrophage function assessment. In studies by Hirschberg et al [14], TSCs were cleared from the bloodstream with nonsaturable kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…However, as MCT are exclusively saturated fatty acids, an essential unsaturated fatty acid such as linoleic acid must be supplemented by blending with LCT for the nutritional requirement of the patients. Several investigators reported that a mixture of intravenously injected MCT/LCT was more advantageous as an energy source under seriously stressful conditions than LCT or glucose [11][12][13]. However, effects of enteral administration of MCT/LCT in sepsis have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…MCT are oxidized independently of carnitine, whereas LCT require carnitine to be oxidized. Jensen et al [13] suggested that MCT would be a promising fat substrate for septic patients who were carnitine-depleted. As MCT were previously reported to be superior to LCT as an energy source in septic rats [21], in the present study we investigated the effect of MCT administration on protein metabolism in septic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em estudos experimentais e clínicos, TCL ω-6 foram associados à deficiência de funções de linfócitos, neutrófilos e macrófagos (Waitzberg et al, 1996;Jensen et al, 1990;Sedman et al, 1990;Hamawy et al, 1985;Sobrado et al, 1985;Nordenstrom et al, 1979). TCL ω-6 podem ainda aumentar a intensidade da resposta inflamatória em determinadas condições clínicas (Wanten e Calder, 2007).…”
Section: Impacto Das Emulsões Lipídicas Sobre O Sistema Imuneunclassified